2018
DOI: 10.1055/s-0038-1636837
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Instrument Can Improve Functional and Radiographic Results during Learning Curve for Oxford Unicompartmental Knee Arthroplasty

Abstract: The true value of use of patient-specific instrumentation (PSI) systems by inexperienced surgeons during their learning curve to improve the clinical and radiographic outcome of unicompartmental knee arthroplasty (UKA) has not been previously studied. Fifty patients with a mean age of 64.3 years undergoing surgery for Oxford UKA were prospectively divided into two groups. Twenty-five patients were operated on by a surgeon with no prior experience in UKA using a PSI system and the other 25 patients by an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Secondly, all surgeries were performed by a single surgeon and at a single surgical center. Many studies con rmed surgeon experience was not only essential for achieving good results in joint arthroplasty but also for affecting the revision rate because each surgeon may classify the causes of revision differently [25,35,36]. Thirdly, the mean follow-up time was not long enough, and small sample size in both cohort groups.…”
Section: Preoperative Resultsmentioning
confidence: 99%
“…Secondly, all surgeries were performed by a single surgeon and at a single surgical center. Many studies con rmed surgeon experience was not only essential for achieving good results in joint arthroplasty but also for affecting the revision rate because each surgeon may classify the causes of revision differently [25,35,36]. Thirdly, the mean follow-up time was not long enough, and small sample size in both cohort groups.…”
Section: Preoperative Resultsmentioning
confidence: 99%
“…However, these two RCTs were conducted by expert UKA surgeons in high-volume centres, so an alternative interpretation is that PSI allows surgeons to replicate expert results. Two previous studies have examined the role of PSI for inexperienced surgeons [ 25 , 26 ]. A small sawbone study of 16 trainee surgeons, who performed lateral UKA using CT-based PSI and conventional instruments, found no difference in accuracy of implant alignment in the coronal, sagittal, or axial planes between the techniques [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small sawbone study of 16 trainee surgeons, who performed lateral UKA using CT-based PSI and conventional instruments, found no difference in accuracy of implant alignment in the coronal, sagittal, or axial planes between the techniques [ 25 ]. However, a recently published clinical trial comparing 25 medial UKA performed using MRI-based PSI by a surgeon with no prior UKA experience, and 25 performed using conventional instrumentation by a surgeon ‘with wide experience’ of UKA, found no difference in tibial component alignment, patient reported outcome scores, or 2-year survival rates [ 26 ]. It should be noted that only coronal plane positioning was specified pre-operatively and unfortunately no detail was given regarding the training received by the one inexperienced UKA surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The PSI technology strives for an improved alignment and component position with custom-fit cutting blocks and guides designed preoperatively to fit the patient's anatomy of the knee [1]. However, expert, high-volume surgeons often have been reported to achieve the same radiological accuracy for TKA with the conventional technique and with PSI [5,6]; The cutoff number ranges 13-50 procedure yearly for TKA to separate low-volume surgeons from high-volume surgeons [7]. The study of Kizaki et al reported 336 patients including 29 patients with bilateral lateral femoral bowing (> 5°) receiving TKAs in a 3-year-long study period from the same surgeon.…”
Section: Expert Vs Trainee Surgeonmentioning
confidence: 99%
“…The large number of cases indicates a highvolume surgeon making careful preoperative planning with long films before conventional TKAs, which could hardly be outperformed by using the PSI. Notably, one of the main advantages of the use of PSI that can increase patient safety during the learning curve of novice surgeons, as PSI might allow non-expert surgeonseven with no prior experience-to achieve the same level of accuracy as expert surgeons [5,6,8].…”
Section: Expert Vs Trainee Surgeonmentioning
confidence: 99%